2021
DOI: 10.1108/ecam-07-2021-0581
|View full text |Cite
|
Sign up to set email alerts
|

Will contractors pursue unsustainable practices following environmental recovery? A highway case in China

Abstract: PurposeThis study aims to map out contractors' thoughts on construction-related environmental recovery as an excuse for deliberately carrying on unsustainable construction.Design/methodology/approachA typical highway construction project in China was investigated. Textual materials were collected through semistructured interviews. Content analysis was conducted to derive qualitative data from the textual materials.FindingsThe research findings reveal a trend of environmental recovery associated with constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…(2009), Serpell et al. (2013), Shokri-Ghasabeh and Chileshe (2014), Shang et al. (2021) and Fitrian and Ajayi (2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2009), Serpell et al. (2013), Shokri-Ghasabeh and Chileshe (2014), Shang et al. (2021) and Fitrian and Ajayi (2022).…”
Section: Methodsmentioning
confidence: 99%
“…measuring the constructs of the conceptual model. Resources, managerial, and regulatory barriers to the implementation of sustainability practices in HRC projects were measured with a 21-item scale adapted from various sources, namelyPitt et al (2009),Serpell et al (2013), Shokri-Ghasabeh and Chileshe (2014),Shang et al (2021), and Fitrian andAjayi (2022). The level of implementation of sustainability practices (i.e., sustainable construction materials, sustainable construction design, modern construction methods, environmental provision and reporting) was measured with a 24-item scale adapted from multiple sources such asTan et al (20211),Armstrong and Davis (2013),Huang et al, (2013),Hearn and Shakya (2018),McGuire and Morrall (2020), andAranda et al (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These repercussions encompass water and soil erosion, the destruction of vegetation, and the disruption of terrains [27]. The construction of railways can also have adverse effects on vegetation, permafrost layers, and land stability [28], leading to water and soil erosion, the desertification of land, and the degradation of grasslands [29]. In contrast, the construction of transportation infrastructure can also yield favorable environmental outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This portrays the devastating impacts of construction activities on construction sites. Furthermore, Shang et al (2021) found loopholes in environmental recovery plans that enable contractors to embrace unsustainable construction practices without being noticed. Considering the issue of materials waste and misuse of natural resources, Harit and Kumar (2021) assessed the sustainability aspect of the expanded polystyrene (EPS) core panel system in terms of cost, energy consumption, carbon dioxide (CO 2 ) emissions and comfort.…”
Section: Ranking Of the Unsustainable Construction Practicesmentioning
confidence: 99%